PENGARUH SARANA DAN PRASARANA LABORATORIUM TEKNIK KOMPUTER JARINGAN TERHADAP KOMPETENSI SISWA DI SMKT SOMBA OPU KABUPATEN GOWA - Nurhuda; Muhammad Yahya; Yusuf Mappeasse (UNM Journal of Technology and Vocational, 2023)
Competence at Somba Opu Vocational School, Gowa Regency. (guided by: Muhammad Yahya and Muh Yusuf Mappeasse). This study aims to determine: (1) The effect of the level of adequacy of practice facilities and infrastructure in the TKJ Laboratory on student competence at SMK Somba Opu Technology, Gowa Regency; (2) The effect of the level of up-to-date practice facilities and infrastructure in the TKJ Laboratory on student competence at Somba Opu Technology Vocational School, Gowa Regency; (3) The effect of learning motivation on student competency at the Somba Opu Vocational School of Technology, Gowa Regency; (4) The simultaneous influence of the adequacy of facilities and infrastructure, the up-to-date facilities and infrastructure and learning motivation on student competence at SMK Somba Opu Technology, Gowa Regency. This type of research is descriptive quantitative research with an ex-post facto approach. The sample in this study was 90 students. Research data obtained by questionnaire and documentation techniques. The data analysis technique used was descriptive statistical analysis and multiple regression analysis. The research results show that; (1) there is a significant effect of the level of adequacy of practice facilities and infrastructure in the TKJ Laboratory on student competence of 7.9%, (2) there is a significant effect of the level of up-to-date practice facilities and infrastructure in the TKJ Laboratory on studentcompetency of 4.7%, (3) there is a significant effect of learning motivation on student competence of6.7%, there is a joint effect of adequacy of facilities and infrastructure, up-to-date facilities andinfrastructure and learning motivation on student competence in Somba Opu Technology VocationalSchool, Gowa Regency of 16.2 %